3D Printing of Graphite Electrode for Lithium‐Ion Battery with High Areal Capacity. Issue 11 (29th September 2021) - Zhang, Fu; Wu, Kaimin; Xu, Xi; Wu, Wenzheng; Hu, Xue; Yu, Kaifeng; Liang, Ce
Abstract : Combined with the traditional preparation method of graphite anode slurry for lithium battery and the manufacturing technology of pneumatic jet, the organic solvent‐based anode slurry is selected to explore the viscosity curve under different solid–liquid ratios. It is judged that the anode slurry is a non‐Newtonian fluid. It has printability and meets the requirements of direct writing molding technology. The slurry with a solid volume fraction of 50% is selected as the printing material, the graphite anode slurry is molded on the copper foil by a pneumatic printing device and the electrochemical performance of the coin lithium‐ion battery is analyzed. The effect of printing structure and printing interval on the electrochemical performance of lithium‐ion batteries is studied and compared with batteries prepared by traditional coating processes. Finally, the linear electrode pattern is selected to discuss the effect of printing layers on the electrochemical performance of lithium‐ion batteries. The results show that the areal specific capacity of the printed electrode is significantly higher than that of the traditional coated electrode and the shape, interval, and the number of layers of the printing electrode have a significant effect on the performance of the battery. Abstract : Herein, 3D printing technology is used to prepare printed electrodes from a graphite slurry. Compared with the traditional coated electrodes, the specific capacity of the printed electrode has been significantly improved. In addition, the shape, spacing, and number of layers of the printed electrode all have a significant impact on the batteries' performance.